Information Technology Tools for Mental Resilience Training in Sports: A Systematic Review - Geoff Dumsday; Thean-Hock Yeoh (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The aim of this research study is to determine the information technology tools related to mental resilience training in sports. This research study determines the primary data for measuring the relation between dependent and independent. For this purpose, develop research questions related to information technology tools and mental resilience. Research determines through smart PLS software and generates informative results related to variables. The descriptive statistical analysis, the correlation coefficients, and the significant analysis also present the co-linearity statistical analysis between them. A systematic and deliberate procedure termed mental resilience training aims to increase a person's ability to deal with stress, obstacles, and adversity successfully. It entails developing the mental capacities and attitudes required to recover from failures, stay focused under duress, and persevere in the face of adversity. The overall research study found the significant and direct effect of information technology tools and mental resilience training in sports.